Do they learn to teach science from their previous teachers? - (:unkn) unknown (Sakarya University, 2015)
This study aims to determine effects of teaching methods and techniques used by their previous teachers on science teachers’ and preservice science teachers’ curiosity and interest to learn science. In this study, it is intended to investigate effect of teachers’ applications in the past that was remained in science teachers’ and preservice teachers’ memory and help them increase their demand and curiosity to learn science and also to lead them to be a science teacher. For the purpose of this study, preservice teachers studying at one of the institution and science teachers graduated at the same institution are chosen by easily accessible sample method. This qualitative study is peformed as a survey. Data were collected through semi-structured interviews as one of the qualitative data collection techniques. Data obtained from the study was analysed by using content and descriptive analysis techniques and interpreted by the reserachers. It was found that, science teachers and perservice science teachers mostly remember (80%) lectures and writing lecture notes among their previous teachers’ teaching methods and techniques. On the other hand, results showed that instead of lectures, they preferred experimentation, making projects, watching animations, researching and presentation methods. Science teachers and preservice science teachers stressed that these methods and techniques are interesting, intriguing and they provide learning by doing, connect with real life, objectify and visualize the content. © The Turkish Online Journal of Educational Technology.
Keywords: Preservice science teachers; Science teachers; Science teaching; Teaching methods and techniques